(untitled) (Research, Society and Development, 2023)
The vegetal species sucupira (Pterodon emarginatus Vogel) presents some diterpenes that have anti-inflammatory activities. However, diterpenes are poorly water-soluble compounds. The development of Self-Emulsifying Drug Delivery Systems (SEDDS) allows for obtaining a solid dosage form that maximizes the release of P. emarginatus constituents in an aqueous medium. This work aimed to obtain and characterize pellets containing the SEDDS prepared from P. emarginatus extract using the extrusion-spheronization technique. Formulations PF1 to PF6 were tested. Then, self-emulsifying formulations were prepared (SES1 to SES5) based on the mixture of poloxamer 188 (Pluronic® F-68) and sorbitan triolate (Span®85) with P. emarginatus extract. Next, formulation PF6, containing microcrystalline cellulose: P. emargitus extract: aerosil®200: polyvinylpyrrolindone K-30 (50: 54.25: 4: 4) was used in the preparation of pellets containing the self-emulsifying systems. These pellets had a homogeneous surface and average sphericity of 0.52. When encapsulated in hard gelatin capsules, it was noted that the formulations PF6, PSES3 and PSES4 were statistically different from each other at the 5% level. In the first 10 min of dissolution, PSES3 and PSES4 showed a higher level of geranylgeraniol released compared to the PF6 (p=0.000117). However, after 20 min of dissolution, no significant difference was observed in relation to the content of this compound. In the accelerated stability study, the average content of the geranylgeraniol was 85.6% and 81.8% for PSES3 and PSES4, respectively, whereas it was only 34.4% for PF6. Under the studied conditions, obtaining the self-emulsifying systems made it possible to achieve the desired dissolution and chemical stability of geranylgeraniol.